Changes in Blood-borne Infection Risk Among Injection Drug Users - Mehta, Shruti H. (Oxford University Press, 2011)
(See the editorial commentary by Grebely and Dore, on pages 571–4.) Background. Population-level hepatitis C virus (HCV) infection incidence is a surrogate for community drug-related risk. Methods. We characterized trends in human immunodeficiency virus (HIV) and HCV infection incidence and HCV infection prevalence among injection drug users (IDUs) recruited over 4 periods: 1988–1989, 1994–1995, 1998, and 2005–2008. We calculated HIV and HCV infection incidence within the first year of follow-up among IDUs whose test results were negative for these viruses at baseline (n = 2061 and n = 373, respectively). We used Poisson regression to compare trends across groups. Results. HIV infection incidence declined significantly from 5.5 cases/100 person-years (py) in the 1988–1989 group to 2.0 cases/100 py in the 1994–1995 group to 0 cases/100 py in the 1998 and 2005–2008 groups. Concurrently, HCV infection incidence declined but remained robust (22.0 cases/100 py in the 1988–1989 cohort to 17.2 cases/100 py in the 1994–1995 cohort, 17.9 cases/100 py in the 1998 cohort, and 7.8 cases/100 py in the 2005–2008 cohort; P = .07). Likewise, HCV infection prevalence declined, but chiefly in younger IDUs. For persons aged <39 years, relative to the 1988–1989 cohort, all groups exhibited significant declines (adjusted prevalence ratio [PR] for the 2005–08 cohort, .73; 95% confidence interval [CI], .65–.81). However, for persons aged ≥39 years, only the 2005–2008 cohort exhibited declining prevalence compared with the 1988–1989 cohort (adjusted PR, .87; 95% CI, .77–.99). Conclusions. Although efforts to reduce blood-borne infection incidence have had impact, this work will need to be intensified for the most transmissible viruses, such as HCV.